Current state and perspectives of securitization processes in the Russian Federation - Koniagina Mariia Nikolaevna (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2020)
Purpose: The study is aimed not only at determining the current state of the bank asset securitization market but also at developing methods and ways to improve the processes of bank asset securitization in Russia. Design/methodology/approach: The article presents the results of a survey of Russian market securitization over the last 10 years, where the author separately considers mortgage and non-mortgage securitization, conducts a discrete analysis of regulatory changes in securitization, and identifies the main problems in the development of this important economic process and the issues that have remained unresolved during the decade. The main methods of study chosen by the author are systematization, generalization and econometric analysis. Finding: The author has demonstrated that there is a strong inverse relationship between the mortgage lending volume and the interest rate, and has built a linear function of the estimated mortgage lending volume. The excess in the real mortgage lending volume over the estimates confirms that the current state policy, including state support and reduction of the Central Bank key rate, in the sphere of mortgage lending is indeed stimulating. Research limitations/implications: The development of securitization in Russia has been constrained not only by sanctions and bureaucratic inconsistencies in the requirements set for securitized assets, but also by delay in the access of the official bodies such as the Federal Service for State Registration, the Cadastre, and Cartography ("Rosreestre") to modern technologies, as well as by the insecurity and distrust of digital financial service technologies.Quite different conclusions follow from the analysis of non-mortgage securitization, where the author supports and develops critical remarks expressed by other researchers in previous years. Originality/value: The survey results not only show the achievements of mortgage lending in Russia in recent years, but also provide valuable recommendations to help support the positive dynamics of mortgage lending and securitization development in the Russian Federation.
Keywords: G18; G21; G23; 330; Securitized assets; Mortgage; Mortgage bonds; Mortgage loan; Commercial bank; Securitization